STUDY ON THE IMPORTANCE OF EARLY AND CONTINUOUS APPLICATION OF INETIC TREATMENT IN PATIENTS SUFFERING FROM ANKYLOSING SPONDYLITIS - Elena Rabolu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The purpose of this paper was to implement a kinetic program intended to improve the symptomatology of the patient with spondylitis, thus increasing their quality of life. The case study has been conducted on a patient aged 49 years diagnosed with spondylitis when he was 24 years old. The therapeutic intervention consisted of applying a series of physical exercises, corrective postures and breathing exercises targeted on the achievement of the objectives relating to the patients suffering from ankylosing spondylitis 'recovery. The analysis of results from the two tests carried out (OTT and BASDAI indexes) revealed that the kinetic programs are an important and instrumental component in treating the patient with spondylitis, proof of which is this research demonstrating that, although it is a progressive disease, by applying a sustained therapy program, it was kept under control, the patient feeling much better from the point of view of the painful episodes, but also as a mobilization option. To conclude, the treatment for ankylosing spondylitis supposes an active and aware participation of the patient in a program of exercises to maintain patient's muscle tone and mobility in their day to day activities.